The Role of T Cells in Hematopoietic Stem Cell Engraftment. (2006) - Hexner, Elizabeth
Abstract : Much attention has focused on the immune recovery of donor T cells following hematopoietic stem cell transplantation (HSCT). Termed immune reconstitution, a better understanding of the dynamics of the functional recovery of immune cells following HSCT has important implications both for fighting infections and, in the allogeneic setting, for providing antitumor activity while controlling graft-vs.-host disease (GVHD). The immune cells involved in immune reconstitution include antigen-presenting cells, B lymphocytes, natural killer cells, and, in particular, T lymphocytes, the immune cell that will be the subject of this review. In addition, T cells can play an important role in the process of engraftment of hematopoietic stem cells. The evidence for a T cell tropic effect on hematopoietic engraftment is both direct and indirect, and comes from the clinic as well as the research lab. Animal models have provided useful clues, but the molecular mechanisms that govern the interaction between donor stem cells, donor T cells, the host immune system, and the stem cell niche remain obscure. This review will describe the current published clinical and basic evidence related to T cells and stem cell engraftment, and will identify future directions for translational research in this area.